Voltaire on war and peace - Meyer, H (Voltaire Foundation, 2017)
Introduction I. Voltaire and the wars of his time A. First third of the century B. The war of the Austrian succession C. The Seven years' war D. Catherine and the Turks E. The war of American independence II. Ideas on war and peace A. War: necessary evil B. War and theft C. War: an organized venture D. Article: 'War' E. War and l'infâme F. War and mankind G. War and law H. War and peace I. War and anti-war projects III. The art of war IV. The soldier, the hero and the great man A. The soldier B. The hero and the great man V. War in poetry and prose VI. Voltaire and the pacifist current in the eighteenth century Conclusion Select bibliography